Controlling Interdiffusion, Interfacial Composition, and Adhesion in Polymer Solar Cells. Issue 7 (10th July 2014) - Dupont, Stephanie R.; Voroshazi, Eszter; Nordlund, Dennis; Vandewal, Koen; Dauskardt, Reinhold H.
<x xml:space="preserve">Abstract</x> NEXAFS spectroscopy is used to precisely quantify the interfacial composition and P3HT chain orientation at the weak P3HT:PCBM/PEDOT:PSS interface. An increase of P3HT:PCBM and PEDOT:PSS interdiffusion with post electrode deposition annealing time and temperature is found to be the underlying mechanism for effectively improving the interlayer adhesion, which is essential for the commercial realization of organic photovoltaic devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>